Cardiovascular outcomes of ferric carboxymaltose supplementation for the management of iron-deficient acute and chronic heart failure- a meta analysis. (11th May 2021) - Abdul Razzack, A; Kumar, S; Kumar, R; Khokhar, HT; Pothuru, S; Adeel Hassan, S; Garimella, R; Theja Reddy, K; Mandava, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background-Iron deficiency is prevalent in heart failure patients and is associated with unfavorable clinical outcomes, irrespective of anemia status. The 2016 European Society of Cardiology (ESC) guidelines recommended intravenous ferric carboxymaltose (FCM) for the management of acute and chronic heart failure in symptomatic HF with reduced ejection fraction (EF).  Objective- To determine whether the correction of iron deficiency with ferric carboxymaltose confers better clinical outcomes in patients with acute and chronic heart failure Methods-Electronic databases ( PubMed, Embase, Scopus, Cochrane) were searched from inception to December 28th, 2020. Unadjusted odds ratios (OR) were calculated from dichotomous data using Mantel Haenszel (M-H) random-effects with statistical significance to be considered if the confidence interval excludes 1 and p < 0.05. The primary outcome of interest was cardiac mortality.  Secondary outcomes included first hospitalisation due to worsening heart failure and any other cardiovascular (CV) reason. Results-A total of five studies with 2091( FCM = 1125; placebo = 966) patients were included. Average follow-up period was 2 years. There was no difference in terms of cardiac mortality (RR 0.93, 95% CI 0.71–1.21; p = 0.57; I2 = 0) and hospitalizations for any CV reason (RR 0.83, 95% CI 0.32–2.16; p = 0.70; I2 = 83) with either group at the end of follow-up. As compared to placebo, FCM was associated with significant reduction in hospitalization due to worsening heart failure (RR 0.64; 95% CI 0.41-0.99; p = 0.04; I2 = 56)  Conclusion- Amongst patients with iron-deficient acute and chronic heart failure, treatment with ferric carboxymaltose reduced the risk of heart failure hospitalizations, with no apparent effect on the risk of cardiac mortality and hospitalizations for any other CV cause.